An Essential Role of Innate Lymphoid Cells in the Pathophysiology of Graft-vs.-Host Disease - Shao, Liang; Pan, Shan; Zhang, Qiu-ping; Jamal, Muhammad; Chen, Lu-hua; Yin, Qian; Wu, Ying-jie; Xiong, Jie; Xiao, Rui-jing; Kwong, Yok-lam; Zhou, Fu-ling; Lie, Albert K. W. (Frontiers in Immunology, 2019)
Allogeneic hematopoietic stem cell transplantation (Allo-HSCT) is the only curative treatment for multiple hematologic malignancies and nonmalignant hematological diseases. However, graft-versus-host disease, one of the main complications after allo-HSCT, remains the major reason for morbidity and nonrelapse mortality. Emerging evidence has demonstrated that innate lymphoid cells (ILCs) play a nonredundant role in the pathophysiology of graft-versus-host disease (GVHD). In this review, we will summarize previously published data regarding the role of ILCs in the pathogenesis of GVHD.